STRATEGI PUBLIC RELATIONS PT ANGKASA PURA II (PERSERO) DALAM UPAYA PENGEMBANGAN BANDAR UDARA INTERNASIONAL SOEKARNO-HATTA - Sagiyanto, Asriyani; Habibullah, Trio (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The process of developing the facilities and infrastructure of Soekarno-Hatta Airport, PT Angkasa Pura II (Persero) is committed to being responsible for the impacts that impact the community due to the policy of closing the M1 line. So the right strategy is needed to socialize the policy of PT Angkasa Pura II (Persero) before closing the M1 line with the aim that the Soekarno-Hatta International Airport facilities and infrastructure services can be maximized so that it becomes a convenient public facility and can trigger the attractiveness of domestic and international tourists to visit Indonesia through Soekarno-Hatta International Airport. This study uses qualitative research with a descriptive analysis approach. The results of this study stated that PT Angkasa Pura II (Persero) Public Relations in the effort of M1 Line Closure at Soekarno-Hatta Airport would be better if it focused on the social responsibility approach to all public affected by the closure and transfer of the M1 route of Soekarno-Hatta Airport . Because the demographic, geographical, and psychographic impact becomes a very big impact from the closure of the M1 path.